(3EYGOI gjcdI GdeUGQa (B:s (3OQGSI JWHjbjI (B/s - (3NWGH, LhOJ LYaQs ((3YeGf(B: s (3OGQ OLdI(B, s, 2009)
(3GdefgLjI hhUa eLJeY GdHMK(B- (3GdeSjQI GdJGQjNjI ddLgGR GdeUQaj aj GdYQGb(B- (3EYGOI GdgjcdI(B- (3JLGQH HYV GdOhd aj ejOGf gjcdI GdfXGe GdeUQaj(B- (3GdEWGQ GdYdej ddHMK(B- (3GdESJfJGLGJ hGdeTQhY GdebJQM dEYGOI GdgjcdIs
(3eQGLY U(B.235 (3; edGMb U(B.231 (3; GbJfj (B5 (3fSN SfI (B2010s
Keywords: (3GdGbJUGO GdeGdjs; (3GdHfhcs; (3GdeUGQas